2012
DOI: 10.4049/jimmunol.1103173
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Phosphatidylinositol 3-Kinase (PI3K)δ or PI3Kγ Reduces IL-17 and Ameliorates Imiquimod-Induced Psoriasis-like Dermatitis

Abstract: Psoriasis is a chronic inflammatory skin disease triggered by interplay between immune mediators from both innate and adaptive immune systems and skin tissue, in which the IL-23/IL-17 axis is critical. PI3Kδ and PI3Kγ play important roles in various immune cell functions. We found that mice lacking functional PI3Kδ or PI3Kγ are largely protected from imiquimod (IMQ)-induced psoriasis-like dermatitis, correlating with reduced IL-17 levels in the lesions, serum, and the draining lymph nodes. TCRγδ T cells were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 49 publications
5
70
1
Order By: Relevance
“…This is comparable to psoriasis patients, where a positive correlation between the psoriasis area and severity index score and the serum IL-17 level has been described. 26,27 Elevated IL-17A serum levels have also been reported for the imiquimod-induced psoriasis-like skin disease (≈20-40 pg/ mL in IMQ-treated wildtype mice, barely detectable in control mice), 36 although less in comparison to the K14IL-17A ind/+ mice, which can be explained by the smaller area of affected skin. The elevated IL-17A levels in the serum of the K14IL-17A ind/+ mice were accompanied by increased numbers of CD11b + cells-mostly neutrophil granulocytes-in the blood (Figure 2A-2C).…”
Section: Discussionmentioning
confidence: 87%
“…This is comparable to psoriasis patients, where a positive correlation between the psoriasis area and severity index score and the serum IL-17 level has been described. 26,27 Elevated IL-17A serum levels have also been reported for the imiquimod-induced psoriasis-like skin disease (≈20-40 pg/ mL in IMQ-treated wildtype mice, barely detectable in control mice), 36 although less in comparison to the K14IL-17A ind/+ mice, which can be explained by the smaller area of affected skin. The elevated IL-17A levels in the serum of the K14IL-17A ind/+ mice were accompanied by increased numbers of CD11b + cells-mostly neutrophil granulocytes-in the blood (Figure 2A-2C).…”
Section: Discussionmentioning
confidence: 87%
“…Finally, the phosphatidylinositol 3-kinase/AKT/mammalian target of the rapamycin (PI3K/AKT/ mTOR) pathway is also targeted by HuR cytoplasmic relocalization, as indicated by the Kyoto Encyclopedia of Genes and Genomes occurrences of inositol phosphate metabolism, mTOR, phosphatidylinositol, and insulin signaling pathways. Positive feedback of HuR in the AKT pathway, which is involved in the pathogenesis of psoriasis, (Mitra et al, 2012;Roller et al, 2012;Buerger et al, 2013), has been reported (Singh et al, 2013). G Garcin et al…”
Section: Discussionmentioning
confidence: 93%
“…Using chemical inhibitors has also given insight into the roles of different isoforms, for example a PI3Kd/g inhibitor (IPI-145) led to a decrease in IL-17 production in a model of inflammatory arthritis, suggesting an inhibitory effect on Th17 differentiation (Boyle et al, 2014). Moreover, the blockade of PI3Kd or g reduced IL-17 and ameliorated imiquimod-induced psoriasis-like dermatitis (Roller et al, 2012).…”
Section: Pi3k In the T Cell Responsementioning
confidence: 98%